Prevalence of Plasmodium Infection in District Multan, Punjab, Pakistan - Bukhari, Syed Latif Shah; Aslam, Kashif; Mansoor, Zinnia; Shabir, Ghulam; Tayyab, Muhammad (International Journal of Scientific Research in Biological Sciences, 2021)
Background: Plasmodium infection (Malaria) always remains hazardous for its fatalities worldwide, especially for Pakistan; it is yet endemic in many areas. Out of five types, Plasmodium vivax and Plasmodium falciparum is dominating in Pakistan. P. vivax is more frequent and widely distributed while P. falciparum is more dangerous and deadly in action. This research was conducted for the assessment of Plasmodium infection frequency in human populations of District Multan, Punjab, Pakistan. Methods: Plasmodium type was identified in the blood of high graded fever patients. Immunochromatographic Technique (ICT) as well as thick and thin blood smears procedure was performed at different laboratories of district Multan where the microscopic examination was carried out for the presence of Plasmodium types and its species. Results: Statistically, the current prevalence and distribution of Plasmodium types was estimated in this work. A total of 192 blood samples were examined. The species recovered were P.vivax, P.falciparum and mixed species. The prevalence of P.vivax, P.falciparum and mixed species was 13.02%, 10.41% and 1.041% respectively. Conclusion: Plasmodium vivax had prevalence over Plasmodium falciparum. The number of prevalence species was greater more in males than females. The age-wise prevalence of plasmodium infection revealed that age group 21-30 years had more prevalence over other age group.